Development of Student Creativity Based on Bilateral Cooperation Using the IPO Modification Method - Avicena, Azra Jinggan; Zahidi, M. Syaprin (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2022)
This research aims to elucidate the strategies employed by the Malang City Government in conjunction with MAN 2 Malang City, SMAN 1 Malang City, and SMAN 3 Malang City to foster student creativity. The development of creativity facilitates bilateral cooperation as a final outcome. This research is qualitative in nature, with the primary data collected through in-depth interviews with the Malang City Public Relations department. A number of significant findings emerged. Firstly, the development of student creativity through the IPO method can be detailed as follows: 1) The input phase involves the recruitment of students, facilitated by the Malang City Government, through a delegation system encompassing three schools. This system encompasses the following elements: a superior student system, the tracing of student achievements within the city, and the internalisation of the mission. 2) Process, including preparation (program, segmentation, targets, and time), implementation (organising), and evaluation including follow-up plans and agreements with external parties. 3) Output, including productivity (creative, cultural, and musical economy), innovation, and cooperation with European states. Secondly, the development of creativity has resulted in bilateral cooperation with the country of Andorra in the field of the local economy and cultural performances.